Hello from MrBillDoesMath!
Answer:
Sum = -119,962 ( I hope!)
Discussion:
Let's determine the pattern.
first term: -3
2nd term: (-3) * (-6) = 18 (multiply first term by -6)
3rd term: (18) * (-6) = -108 (multiply 2nd term by -6)
4th term : (-108)*(-6) = 648 ( etc)
5th term : (648)*(-6) = -3888 (etc)
6th term : (-3888)*(-6) = 23328 (etc)
7th term: (23328)*(-6) = -139967 (etc)
Sum = -119,962
A simpler way to do this is to use the formula for the sum of a geometric series to n terms. The series is
-3 Sum ( -6)^n n = 0, 1, 2, 3, 4, 5, 6
Regards,
MrB
P.S. I'll be on vacation from Friday, Dec 22 to Jan 2, 2019. Have a Great New Year!